2009
DOI: 10.1063/1.3206910
|View full text |Cite
|
Sign up to set email alerts
|

Single beam acoustic trapping

Abstract: A single beam acoustic device, with its relatively simple scheme and low intensity, can trap a single lipid droplet in a manner similar to optical tweezers. Forces in the order of hundreds of nanonewtons direct the droplet toward the beam focus, within the range of hundreds of micrometers. This trapping method, therefore, can be a useful tool for particle manipulation in areas where larger particles or forces are involved. © 2009 American Institute of Physics. ͓DOI: 10.1063/1.3206910͔Optical trapping of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
130
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 214 publications
(135 citation statements)
references
References 11 publications
3
130
0
2
Order By: Relevance
“…These studies have shown that Gaussian beams can be used for trapping particles in both axial and transverse directions, although the latter is expectedly much easier. These theoretical findings were also experimentally confirmed using a single focused Gaussian ultrasound beam, for entrapment of very fine lipid droplets (in order of 125 m) [41][42][43]. Besides the transverse entrapment, it was also shown that a high frequency focused beam could be used to laterally move micro-droplets towards the focus point.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…These studies have shown that Gaussian beams can be used for trapping particles in both axial and transverse directions, although the latter is expectedly much easier. These theoretical findings were also experimentally confirmed using a single focused Gaussian ultrasound beam, for entrapment of very fine lipid droplets (in order of 125 m) [41][42][43]. Besides the transverse entrapment, it was also shown that a high frequency focused beam could be used to laterally move micro-droplets towards the focus point.…”
Section: Introductionsupporting
confidence: 51%
“…As a promising result, Lee et al have shown that the proposed acoustic technique offers entrapment over a much wider spatial range than the equivalent optical devices [42,43].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations